1971
DOI: 10.1111/j.1600-0447.1971.tb02138.x
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Conditions of Unwanted Children

Abstract: There were two points of departure for the present investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The relation between low birth weight and bad developmental outcome has been documented in the human as well as in other primate species. In humans, parental rejection and abuse have been related to low birth weight (Hultin & Ottosson, 1971;Klein & Stern, 1971). Retrospective data analyses at our colony showed that smaller infants, if they remained with their mothers, were more likely to die of abuse, malnutrition, or pneumonia than were larger infants (Fredrickson,Note 2).…”
Section: Hierarchical-stepwise Regressionmentioning
confidence: 99%
“…The relation between low birth weight and bad developmental outcome has been documented in the human as well as in other primate species. In humans, parental rejection and abuse have been related to low birth weight (Hultin & Ottosson, 1971;Klein & Stern, 1971). Retrospective data analyses at our colony showed that smaller infants, if they remained with their mothers, were more likely to die of abuse, malnutrition, or pneumonia than were larger infants (Fredrickson,Note 2).…”
Section: Hierarchical-stepwise Regressionmentioning
confidence: 99%